Ca2+-substitution effect on the defect structural changes in the quadruple perovskite series Ca1+xCu3-xTi4O12 studied by positron annihilation and complementary methods. Issue 2 (15th January 2021) - Barad, Divyesh V.; Mange, Priya L.; Jani, Komal K.; Mukherjee, Shubharaj; Ahmed, Maudud; Kumar, Sudhish; Dolia, Satya N.; Pandit, Rabia; Raval, Pooja Y.; Modi, Kunal B.; Nambissan, P.M.G.
Abstract: A series of quadruple perovskites Ca1 +x Cu3 -x Ti4 O12 was scanned by different spectroscopic and microscopic techniques. X-ray powder diffraction pattern analysis revealed that the system transformed from a monophasic ( x  = 0.0, 0.1 and 0.2) to biphasic ( x  = 0.5 and 1.0) on Ca 2+ - substitution. The completely different grain morphology and the distinct signature of the UV–visible absorption band and Raman scattering peak reflect this finding well. The defects arise mainly because of the mismatch between ion and site radii. The results of positron annihilation spectroscopy to study the nature of the defects are consistent with the proposed defect-rich sample history. There are many vacancies-type defects, whose size and concentration could be characterized through the measured positron lifetimes and coincidence Doppler broadening. The results show that for x  = 0.1 itself, a secondary phase may be formed. The structure-property and property-property correlations are studied.